PENDAMPINGAN BAGI ORANG TUA MENJADI PENDIDIK TANGGUH UNTUK ANAK DALAM PEMBELAJARAN JARAK JAUH DI MASA PANDEMIC COVID 19 - Amirah Diniaty; Raja Rahima MRA; Tohirin Tohirin; Riswani Riswani; Fitra Herlinda; Suhertina Suhertina; Hasgimianti Hasgimianti; Deceu Berlian Purnama; Suci Habibah (XXXXX, 2022)
This service aims to provide assistance to parents as educators for children during distance learning (online). The target group for the service activities are parents of students at MTs Foundation Darel Fadhilah Pekanbaru who have voluntarily participated in group guidance. The stages of mentoring activities that have been carried out include 1) preparation of materials, and media, as well as personnel involved in mentoring, 2) Design of assistance products that have been produced in the form of materials, media, schedule and arrangement of mentoring activities and responsible personnel. Some of the problems that have been discussed in this activity are 1) Children use cellphones more to play than study, 2) Parents find it difficult to provide assistance due to reduced manners due to playing cellphones, 3) Broken home family communication problems between parents and children (live separately), 4) The problem of quiet children, difficult to socialize with other people. The last activity that has been carried out is by interviewing participants, and having done a written evaluation. The results of the interviews showed that the members felt the benefits in the form of new insights and knowledge about mentoring children during distance learning.